Linker defects in metal–organic frameworks for the construction of interfacial dual metal sites with high oxygen evolution activity - Ni, Chunyan (2023)
Designing efficient electrocatalysts based on metal–organic framework (MOF) nanosheet arrays (MOFNAs) with controlled active heterointerface for the oxygen evolution reaction (OER) is greatly desired yet challenging. Herein, a facile strategy for the synthesis of MOF-based nanosheet arrays (γ-FeOOH/Ni-MOFNA) is developed with abundant heterointerfaces between Ni-MOF and γ-FeOOH nanosheets by introducing linker defects to the former. The experimental and theoretical results show the key role of linker defects in inducing the growth of secondary γ-FeOOH nanosheets onto the surface of Ni-MOFNAs, which further leads to the formation of interfacial Ni/Fe dual sites with high oxygen evolution activity. Notably, the resulting γ-FeOOH/Ni-MOFNA exhibits excellent OER performance with low overpotentials of 193 and 222 mV at 10 and 100 mA cm−2, respectively. Furthermore, the study of the structure–performance relationship of MOF-based heterostructures reveals that Ni sites at the interface of the γ-FeOOH/Ni-MOFNA have higher activity than those at the interface of NiFe layered double hydroxide and Ni-MOFNA. This study provides a new prospect on heterostructured electrocatalysts with highly active sites for enhanced OER.